2000
DOI: 10.1037/0022-006x.68.4.728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a brief motivational intervention with college student drinkers.

Abstract: This study consisted of a randomized controlled trial of a 1-session motivational intervention for college student binge drinkers. Sixty students who reported binge drinking 2 or more times in the past 30 days were randomly assigned to either a no-treatment control or a brief intervention group. The intervention provided students with feedback regarding personal consumption, perceived drinking norms, alcohol-related problems, situations associated with heavy drinking, and alcohol expectancies. At 6-week follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
447
6
14

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 495 publications
(487 citation statements)
references
References 23 publications
20
447
6
14
Order By: Relevance
“…These improvements exceeded the reductions associated with the TLFB/control condition. Our findings add to the growing literature documenting the efficacy of individually-administered BMIs for at-risk college drinkers (Baer, Kivlahan, Blume, McKnight, & Marlatt, 2001;Borsari & Carey, 2000;Murphy et al, 2004;Murphy et al, 2001). Importantly, this study demonstrated differential improvement compared to two comparison conditions, a standard assessment control and an active TLFB/control condition.…”
Section: Discussionsupporting
confidence: 64%
“…These improvements exceeded the reductions associated with the TLFB/control condition. Our findings add to the growing literature documenting the efficacy of individually-administered BMIs for at-risk college drinkers (Baer, Kivlahan, Blume, McKnight, & Marlatt, 2001;Borsari & Carey, 2000;Murphy et al, 2004;Murphy et al, 2001). Importantly, this study demonstrated differential improvement compared to two comparison conditions, a standard assessment control and an active TLFB/control condition.…”
Section: Discussionsupporting
confidence: 64%
“…Participants were also asked to estimate the number of drinks consumed by the typical student on a given occasion (e.g., "How many drinks on average do you think a typical student at your college consumes on a given occasion?"). This measure has previously demonstrated good convergent validity with measures of drinking (Baer et al, 1991;Borsari & Carey, 2000;Neighbors, Larimer, & Lewis, 2004).…”
Section: Methodsmentioning
confidence: 98%
“…Although brief feedback interventions for alcohol use have traditionally been delivered by more conventional face-to-face (e.g., Humpreys and Klaw, 2001;Borsari and Carey, 2000) and postal mail methods (e.g., Collins et al, 2002; Walters et al, 2000;Agostinelli et al, 1995), they have more recently been delivered electronically via computer programs (e.g. Neighbors et al, 2004; Matano et al, 2000) and the internet (e.g., Davies-Kirsch and Lewis, 2004; Saitz et al, 2004; Kypri et al, 2003;Cunningham et al, 2000).…”
Section: Accepted M Manuscript 3 Inmentioning
confidence: 99%
“…Studies suggest that incorporating social norms information into feedback interventions can help decrease alcohol consumption, encouraging participants to become more aware of the level and consequences of their drinking and how their drinking behaviors compare to others of a similar social or demographic group (White 2006; Walters and Neighbors, 2005; Neighbors et al, 2004;Collins et al, 2002;). Although brief feedback interventions for alcohol use have traditionally been delivered by more conventional face-to-face (e.g., Humpreys and Klaw, 2001;Borsari and Carey, 2000) and postal mail methods (e.g., Collins et al, 2002; Walters et al, 2000;Agostinelli et al, 1995), they have more recently been delivered electronically via computer programs (e.g. Neighbors et al, 2004; Matano et al, 2000) and the internet (e.g., Davies-Kirsch and Lewis, 2004; Saitz et al, 2004; Kypri et al, 2003;Cunningham et al, 2000).…”
mentioning
confidence: 99%